Arabic Language Environment for Islamic Boarding School Student Language Acquisition: Capturing Language Input, Interaction, and Output - Muttaqin, Imam; Bakheit, Bakri Mohamed; Hasanah, Mamluatul (LETIGES, 2024)
This study aims to learn more about the Arabic language environment and its relationship to input, interaction and output in student language acquisition. The approach used is a qualitative approach with a case study type. Determination of informants using purposive techniques. Data collection techniques include observation, interviews, and documentation. Data analysis using the Miles, Huberman and Saldana models, namely data condensation, data presentation, and conclusions. The results of the study show that the Arabic language environment consists of a formal Environment containing classroom learning, Mhārh al-qirāʼah, mhārh al-kitābah, al-Istimāʻ wa-al-kalām, Informal Environment containing language activities outside the classroom; ilqāʼ al-mufradāt, al-muḥādathah, al-tawʻiyah al-dīnīyah, al-khaṭṭ al-ʻarabī, muhadlarah, and maḥkamat al-lughah. Related to input, interaction, and output, the Arabic language environment is concerned with formal and informal environments. The formal environment of language input in the form of structured teacher utterances originates from dialogue and language exercises, patterned language interactions between individual teachers and groups of students and interactions between groups of teachers and groups of students, while the language output is in the form of structured student utterances according to Arabic language structure patterns. While the informal environment of language input in unstructured teacher utterances originates from natural language, the language interaction in it is patterned, the interaction between individual teachers and individual students or vice versa, while the language output is in the form of student utterances obtained naturally. It should be noted that this study is limited to the aspects of the Arabic Language Environment and Language Acquisition. The findings of this study show the importance of an Arabic language environment that can enrich language input, interaction, and output in the language acquisition process.